2006
DOI: 10.2527/jas.2006-157
|View full text |Cite
|
Sign up to set email alerts
|

Retention of different sizes of electronic identification boluses in the forestomachs of sheep1,2

Abstract: Twelve types of electronic identification ruminal boluses of different dimensions were used to obtain a model for predicting their retention in the forestomachs of sheep. Boluses (n = 1,662) were made of ceramic materials, and their dimensions varied in o.d. (9 to 21 mm), length (37 to 68 mm), volume (2.5 to 21.0 mL), and specific gravity (0.85 to 3.91). Each bolus contained a half-duplex, standardized, glass-encapsulated transponder (32 x 3.8 mm). Boluses were administered to sheep (n = 1,497) of different ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
2
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 15 publications
3
23
2
3
Order By: Relevance
“…Thomas et al (2006) reported that the overall loss of e-ETs was 9.9 % for sheep in 4.5 months and 19.2 % for lambs in about 3 months, and these lost rates were unacceptably high for official use. Elec- tronic and visual ear tag losses observed in the study were lower than those reported in the literature (Caja et al, 1999;Conill et al, 2002;Rusk, 2002;Ghirardi et al, 2006;Thomas et al, 2006). …”
Section: Resultscontrasting
confidence: 54%
See 1 more Smart Citation
“…Thomas et al (2006) reported that the overall loss of e-ETs was 9.9 % for sheep in 4.5 months and 19.2 % for lambs in about 3 months, and these lost rates were unacceptably high for official use. Elec- tronic and visual ear tag losses observed in the study were lower than those reported in the literature (Caja et al, 1999;Conill et al, 2002;Rusk, 2002;Ghirardi et al, 2006;Thomas et al, 2006). …”
Section: Resultscontrasting
confidence: 54%
“…Readability of ear tags (96.8 % for e-ETs and v-ETs, 93.5 % overall) placed on the 1/2 part of the ear did not reach the ICAR value, whereas readability of ear tags placed on the 1/3 part of the ear was 99.0 % for e-ETs and v-ETs, and 98.1 % overall at 1 year after tagging as recommended by ICAR. Ghirardi et al (2006) observed a 3.3 % annual loss in plastic ear tags in sheep. Carne et al (2010) also reported 4.3 % of e-ETs and 3.0 % of v-ET losses at 1 year in dairy goats, which was unsatisfactory for official use according to the ICAR requirements.…”
Section: Resultsmentioning
confidence: 99%
“…Readings of ruminal bolus were taken immediately before and after administration to identify precocious losses, as recommended by Ghirardi et al (2006). During 1-ruminal bolus; 2 -big ear tag; 3 -small ear tag.…”
Section: Methodsmentioning
confidence: 99%
“…Electronic ruminal boluses comply with the requirements established by ICAR (2007) and, therefore, are considered safe and effective means of identification of cattle and sheep (Caja et al, 1999;Ghirardi et al, 2006). However, high variability has been observed for retention rate of electronic rumen boluses in goats (Pinna et al, 2006;Carné et al, 2009a;Carné et al, 2009b).…”
Section: Introductionmentioning
confidence: 93%
“…Ear tag losses were 7.5%, while bolus retention varied with bolus features and sheep age. Boluses of 16-45 g, with a volume of 3-22 mL, and specific gravity of 2.0-5.2 were estimated to have a 99.5% retention rate, while boluses of less than 15 mm, specific gravity higher than 3 and weight greater than 20 g were recommended for use in sheep (Ghirardi et al ., 2006b). Ceramic mini-boluses with these parameters did not cause feed intake or growth differences and had 100% recovery at slaughter (Ghirardi et al ., 2007).…”
Section: Ruminantsmentioning
confidence: 99%